DOG DAYS OF CLIMATE CHANGE: HEATING THE DEBATE FOR FEDERAL CAP-AND-TRADE (Utah Environmental Law Review; Vol 28 No 1 (2008), 2009)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} Global warming is a complex issue, but the message resonating across the United States is simple: it is time for action. Corporate leaders, scientists, environmental groups and states from across the country have united because it is no longer a question of whether to take action, but what kind of action to take. Over the past hundred years, the earth has increased its temperature and most scientists agree that this is due to a rise in the main Greenhouse Gases (GHGs): carbon dioxide (CO 2 ), methane, nitrous oxide (NO x ), and fluorocarbons. Several experts believe that this escalation in temperature has already led to severe health and environmental disasters and will continue to cause devastating problems for the environment and for human health.  The United Nations' Intergovernmental Panel on Climate Change (IPCC) has identified the following potential impacts of climate change: severe storms and floods, reduction in crop yields, drying of agricultural land, loss of freshwater resources, loss of fragile ecosystems and wildlife, and an increase in diseases such as malaria.